54th AIAA Aerospace Sciences Meeting 2016
DOI: 10.2514/6.2016-1553
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel Experiments with Flexible Plates in Transonic Flows

Abstract: The evolution of adaptive shock control bump (SCB) design has seen the system flexibility increase to a point where the aerodynamic loading can affect the deformation of the plate. By studying the effects of a flexible plate subject to transonic flow the fluid structure interaction can be investigated. In this study an array of thin plates (0.4 and 0.6 mm) with different aspect ratios (1 and 1.33) are exposed to a Mach 1.4 normal shockwave. PIV is used in combination with Schlieren imaging to provide a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…These dimensions were selected to match the parameters used in a related experimental study in a high speed wind tunnel, the results of which are reported elsewhere [18]. The stream-wise length of the flexible region (200 mm) corresponds to a bump length l b = 0.2c for a nominal aerofoil chord of 1 m. Full fixation against translation and rotation is imposed on the upstream and downstream ends of the flexible region.…”
Section: Structural Modellingmentioning
confidence: 99%
“…These dimensions were selected to match the parameters used in a related experimental study in a high speed wind tunnel, the results of which are reported elsewhere [18]. The stream-wise length of the flexible region (200 mm) corresponds to a bump length l b = 0.2c for a nominal aerofoil chord of 1 m. Full fixation against translation and rotation is imposed on the upstream and downstream ends of the flexible region.…”
Section: Structural Modellingmentioning
confidence: 99%
“…shockwaves. They can be created either passively through a panel that deflects due to the surrounding flow or actively through the usage of actuators placed beneath the panel that deflect it in a controlled manner [13]. shows the drag reduction in the wake for an airfoil with a SCB compared to a clean airfoil.…”
Section: Subsonic Fsimentioning
confidence: 99%
“…The strength of shock bifurcation can be seen to depend heavily on shock location, and the adverse effect of the bump geometry can be seen in the thickening of the boundary layer past the bump with the eventual formation of a shear layer as marked in Figure 1.6f. However, Jinks et al [13] recently investigated in depth both passive and active flow control methods using SCB, and they recommend additional actuators or limit stops to maintain optimal shapes even when in off-design performance conditions. Overall, there is strong evidence towards SCB as a successful application of FSI in the transonic regime.…”
Section: Subsonic Fsimentioning
confidence: 99%